PENINGKATAN KUALITAS DAN PELAYANAN TERHADAP PENGAMBILAN KEPUTUSAN PENDANAAN NASABAH PADA PT. BANK BNI SYARIAH NGANJUK - Respatiningtias, Dyah Suswanti (LIPI, 2019)
This study aims to determine the effect of improving quality and service partially or simultaneously on customer funding decision making at PT. Bank BNI Syariah Nganjuk. This type of research uses quantitative research methods with causal associative research design (cause and effect). Data collection tools used in the form of questionnaires. The sampling technique used uses the Slovin formula with a sampling technique in the form of accidental sampling, ie anyone who accidentally meets a researcher can be used as a sample, if it is deemed that the person met by chance is suitable as a data source. So we get 70 customers who use services at PT. Bank BNI Syariah Nganjuk. The analytical method used is multiple linear regression analysis with partial hypothesis testing using the t statistical test and simultaneous testing using the F statistical test. The results of this study prove that (1) Quality improvement has a partial effect on customer funding decision making at PT. Bank BNI Syariah Nganjuk. (2) Services partially influence the decision making of customer funding at PT. Bank BNI Syariah Nganjuk. (3) Quality and service improvement simultaneously influences the customer's funding decision making at PT. Bank BNI Syariah Nganjuk.